Arabic-speaking women's experiences of communication at antenatal care in Sweden using a tablet application—Part of development and feasibility study. (May 2020) - Bitar, Dima; Oscarsson, Marie
Abstract: Objectives: The purpose of this study was to explore Arabic-speaking women´s experiences of communication at antenatal care in Sweden when using a tablet application (app). Design: The study is a part of a major research project, where a Swedish-Arabic app was developed to improve and facilitate communication between Arabic-speaking women and midwives. The first prototype was developed in 2017 and tested at six antenatal clinics in southeast of Sweden. Ten Arabic-speaking women were purposively recruited, and individual interviews were performed. Content analysis was used. Findings: Four main categories emerged: "Adapting the content to the patient group", "language and communication", "user-friendly" and "improvement proposal". The women reported that the content was educational, reliable and understandable. The information gave the women a sense of security. It was time effective and allowed opportunity for dialogue. Depending on language skills, there were different opinions as to whether the App should be a complement to having an interpreter or used separately. Key conclusion: Arabic-speaking women perceived the App as being a communication tool despite their language skills in Swedish. There is a need for digital support for communication in maternity care.